El símbol de la rosa en l’obra poètica de Josep Palau i Fabre: evolució i contrastos - Anna Perera Roura (Catalonia)
The article analyzes the treatment and the evolution of the symbol of rose in the poetry of Josep Palau i Fabre. The rose is a fundamental element in the symbolism of Western culture and has an extensive literary tradition. However, in the poetry of Palau i Fabre, the rose is a symbol that takes on different meanings, which are transformed over time. Therefore, based on the analysis of the evolution of the rose in his poetic work, we can confirm that this element also represents the aesthetic evolution of Palau i Fabre: a poetic revolt within the Catalan literary tradition.